Pengembangan Media Edukasi Interaktif Berbasis Flipbook Maker dalam Upaya Pencegahan Stunting - Lestari, Nia; Yulia, Cica; Subekti, Sri; Muktiarni, Muktiarni (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2023)
The purpose of this research is to develop flipbook maker-based interactive educational media (e-books) as an effort to prevent stunting, the objectives of this research are: 1) to develop user-friendly and customized e-book design stages for stunting prevention. 2) Designing flipbook-based e-books for Posyandu cadres to improve or strengthen the knowledge, attitudes, and literacy of individuals/young mothers in preventing stunting. 3) Knowing the feasibility of the developed flipbook-based e-book. The research method refers to the method that has been developed by Villamil-Molina which consists of four stages, namely development, preproduction, production, postproduction. The instruments used in this study consisted of material expert validation sheets, media and language validation sheets. The results of this study are flipbook-based Interactive Educational Media that are appropriate to use which have gone through the validation process of media experts and material experts. The research results are expected to be a solution to the problem of stunting in West Java.Kata kunci: Media edukasi interaktif, Flipbook, Stunting